2005
DOI: 10.1051/0004-6361:20041989
|View full text |Cite
|
Sign up to set email alerts
|

Strong dust processing in circumstellar discs around 6 RV Tauri stars

Abstract: Abstract. We present extended Spectral Energy Distributions (SEDs) of seven classical RV Tauri stars, using newly obtained submillimetre continuum measurements and Geneva optical photometry supplemented with literature data. The broad-band SEDs show a large IR excess with a black-body slope at long wavelengths in six of the seven stars, R Sct being the noticeable exception. This long wavelength slope is best explained assuming the presence of a dust component of large grains in the circumstellar material. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 26 publications
6
64
0
3
Order By: Relevance
“…Many of them have already been given a disc status in the literature (de Ruyter et al 2006;De Ruyter et al 2005). The 63 (50%) RV Tauri stars, in the non-IR box do not display any IR excess at all, also not when considering their full SED.…”
Section: Rv Tauri Starsmentioning
confidence: 99%
“…Many of them have already been given a disc status in the literature (de Ruyter et al 2006;De Ruyter et al 2005). The 63 (50%) RV Tauri stars, in the non-IR box do not display any IR excess at all, also not when considering their full SED.…”
Section: Rv Tauri Starsmentioning
confidence: 99%
“…Contrary to U Mon, R Sct has not been found to be part of a binary system (de Ruyter et al 2005). The latter authors also pointed out the much lower dust excess in R Sct compared to U Mon with drastically different spectral energy distributions.…”
Section: Discussionmentioning
confidence: 90%
“…Our magnetic field measurements in the photosphere of U Mon and R Sct support the use of weak fields in MHD models. In addition, de Ruyter et al (2005) suggested that U Mon hosts a "non-spherically symmetric circumstellar dust distribution" based on the comparison of its large IR excess and the lack of line-of-sight reddening. The strong Stokes Q and U profiles presented in Fig.…”
Section: Influence Of the Weak Field On The Dynamicsmentioning
confidence: 99%
“…The discs are spatially resolved, but this is only detectable using interferometric techniques (Deroo et al 2006(Deroo et al , 2007, and they typically have a radius of only 50 AU at 10 μm. The high dust-grain processing is an observational indication that the compact discs are stable (De Ruyter et al 2005;Gielen et al 2008Gielen et al , 2009. Since the discovery of the binary nature of a small sample of the most depleted objects (Van Winckel et al 1995), this binary nature of the disc sources has been further confirmed ).…”
Section: Introductionmentioning
confidence: 94%